Continuum Colonial: colonialidade (=modernidade), empreendimentos capitalistas, deslocamentos compulsórios e escravos da República no Estado do Maranhão, Brasil - MENDONÇA, Bartolomeu Rodrigues (2017)
This thesis contests current and academic understanding of modernity as the expression of a civilized and superior humanity in all of its dimensions (social, political, economic, cognitive, moral) which would have in coloniality its unwanted side effect, and would allegedly have been overcome or is on its way to. Instead, it pursues to demonstrate that a conceptualanalytical inversion is possible: what has endured and is currently being deepened, is the coloniality that emerged in the fifteenth century, with the beginning of European empires great navigations towards the conquest of the new world – as they named it themselves; and modernity figures as economic, political, cognitive benefits, and so on, restricted to the settlers, or their reduced and dependent caste of subjects, the fruit of looting, theft, the death of coloniality’s victims, presently updated and deepened by the colonial heir elite. There is therefore the worldwide expression of coloniality (=modernity) which suggests the colonial continuum as an analytical proposition. To demonstrate the thesis of coloniality (=modernity) and the colonial continuum, the empirical situations of compulsory displacements were chosen, and the expropriation of territory, resources, products, knowledge and population government resulting from them. The colonial elite, as well as their inheritors, who have promoted primitive accumulation through despoliation, have at the same time profited from the expropriation and exploration of territories and the work force of Indigenous and African peoples and other peoples or traditional communities – currently the republic slaves. The debate over modernity, transmodernity, coloniality, development, progress, globalization, although controversial, has constituted the fundamental for the thesis main hypothesis: compulsory displacements due to planning, installation and operation of massive projects of intensive development in land, capital and workforce, which hierarchize human social groups, as well as their territories in civilized/barbarian or qualified/unqualified presently occur as unfoldings of a colonial modus operandi - by means of the colonial continuum. To demonstrate this hypothesis, as well as to furnish this thesis, besides drawing from a large academic production (ranging from contributions from Marx, 1985; Benjamin, 1987; Harvey, 2010; Foucault 2008; Ianni, 2000; to the those named post or de-colonial Latin Americans such as Dussel, 2005; Mignolo, 2003; Quijano, 1992), and speeches classified as common sense, contained in narratives, in conversations of people in traditional communities or presently circulating in pamphlets, newspapers and websites are also considered. The typical empiricists analysed who turn into privileged status of entities for inference were the RESEX communities in Tauá-Mirim, in Área Rural II, São Luis/MA, the Piquiá de Baixo community in Açailândia/MA, and the Projeto Pioneiro de Colonização in Buriticupu/MA.